Operative cystoscopy in the neonatal period - Salvatore Arena; Tiziana Russo; Patrizia Perrone; Carmelo Romeo (PAGEPress Publications, 2016)
Aim of the study is to report the experience in the last three years about endourological treatment of newborns affected by genito- and urinary malformation, implying critical urinary tract dilatation and bladder mass requiring a neonatal operative management. Seven - four males and three female - patients were treated cystoscopically during the neonatal period. Three newborns with a posterior urethral valves (PUV), underwent a successful ablation of PUV. In a male with infected persistent large mullerian duct and subsequent acute urinary retention, a cystoscopically-assisted catheterization was performed. Two females, one with cloaca and the other with high persistent urogenital sinus and massive associated hydrometrocolpos underwent a cystoscopical drainage of the vagina and a positioning of a balloon catheter into the bladder. Another female with a bladder mass had a endoscopical biopsy. Thanks to modern neonatal operative urethrocystoscope, today is possible to treat early many pathological genito-urinary conditions in newborns.